The Development Of Gamification-Based Learning Media “AKUBI: Akuntansi Biaya (Cost Accounting)” at SMK Muhammadiyah 2 Malang - Firdausi, Fina Melika; Putri, Sheila Febriani (Sosio-Didaktika: Social Science Education Journal, 2025)
Technological advances in the Society 2.0 era require educators to be able to create learning media that is integrated with digital technology. Observations and interviews at SMK Muhammadiyah 2 Malang revealed that there were several problems faced, especially in the Accounting subject, including a lack of variety in learning media, Cost Accounting material which was classified as difficult causing students to be unmotivated to learn, and the tendency of students to play with gadgets when learning taking place. This research aims to develop "AKUBI: Akuntansi Biaya", a gamification-based learning media, and measure its effectiveness on learning motivation. The method used is Research and Development (R&D) with the ADDIE model. The results of the validation test by experts (media experts, programming experts and material experts) obtained a percentage of 92.10% in the very feasible category and the student response to the media was 90,86% which was categorized as very feasible. The n-gain measurement results show an increase in learning motivation of 0.58 (medium category) and 57.84%, which means that gamification media is quite effective in increasing learning motivation. Thus, the "AKUBI" media is very suitable for use in Cost Accounting lessons and is able to provide new learning experiences, increase motivation, and make it easier to understand difficult material.